A 120°C 20G-compliant vibration energy harvester for aeronautic environments. (November 2019) - Gasnier, P; Boucaud, M; Gallardo, M; Willemin, J; Boisseau, S; Morel, A; Gibus, D; Moreau, M
Abstract: This paper reports the design, fabrication and testing of a piezoelectric energy harvester operating at 90°C and withstanding 120°C and 20G of acceleration. This harvester, along with its dedicated power management circuit, has been designed to supply a 3-channel Acceleration Measurement System (AMS) for the structural health monitoring of an aircraft engine. This aeronautic-compliant bimorph harvester outputs 6.83mW at 1G, up to 246mW at 8G of acceleration and exhibits a maximum Normalized Power Density of 15.3kg.s.m − 3 at 90°C.